Effects of phosphorus-solubilizng bacteria on plant development and soil microbiology - Martins, Mayara Martins e (2024)
Phosphate-solubilizing microorganisms play a crucial role in the growth and development of plants, directly influencing the availability of phosphorus (P) and, consequently, plant development. This study investigates how these solubilizers affect not only plant nutrition but also changes in soil microbiology, assessing their contribution to soil health and fertility. By exploring the interaction between P solubilizers, plants, and soil microbiota, the aim is to deepen the understanding of sustainable agricultural practices, promoting efficient nutrient use and stimulating plant development in specific environments through the use of phosphate-solubilizing microorganisms. The objective of this study was to evaluate the performance of the association between phosphate sources and potentially phosphate-solubilizing microorganisms, focusing on plant nutritional uptake and soil impact. Following a detailed analysis of the mechanisms and functions of phosphatesolubilizing microorganisms in the context of global P challenges, an experiment was conducted in a greenhouse, covering two scenarios: residual fertilization management, based on historical fertilization practices (with TSP or RRP), and fresh fertilization management, involving the direct application of fresh fertilizer (TSP or RRP). Both scenarios were subjected to the inoculation factor (with or without inoculation of the ATCC 7061 isolate classified as Bacillus pumilus). The experimental design was a randomized complete block design in a factorial scheme (2 × 2). Plant material was collected for analysis of leaf contents of N, P, K, Ca, Mg, and S. Fertility assessments included determinations of P, K, Ca, and Mg levels, organic matter (OM), pH, H + Al, and cation exchange capacity (V%). For microbial community analysis, determinations of acid phosphatase and beta-glucosidase, as well as microbial P quantification, were performed. Although the use of phosphate-solubilizing microorganisms has the potential to enhance the absorption of phosphate fertilizers by plants, no positive changes in soil P fractions were observed after bacterial inoculation as expected, indicating the need for further studies to understand this interaction. However, an increase in the non-labile P fraction was observed in treatments with Recalcitrant Rock Phosphate (RRP) and Triple Superphosphate (TSP), suggesting bacterial activity in rock degradation processes in both fresh and residual scenarios.